Do not Bet on the Unknown Versus Try to Find Out More: Estimation Uncertainty and “Unexpected Uncertainty” Both Modulate Exploration - Payzan-LeNestour, Elise; Bossaerts, Peter (Frontiers in Neuroscience, 2012)
Little is known about how humans solve the exploitation/exploration trade-off. In particular, the evidence for uncertainty-driven exploration is mixed. The current study proposes a novel theory of exploration that helps reconcile prior findings that may seem contradictory at first. According to this theory, uncertainty-driven exploration involves a dilemma between two motives: (i) to speed up learning about the unknown, which may beget novel reward opportunities; (ii) to avoid the unknown because it is potentially dangerous. We provide evidence for our theory using both behavioral and simulated data, and briefly point to recent evidence that the brain differentiates between these two motives.